2020
DOI: 10.1002/jac5.1376
|View full text |Cite
|
Sign up to set email alerts
|

Impact of remote delivery on a pharmacists' patient care process capstone course on the development of patient work‐up skills

Abstract: IntroductionThe coronavirus disease 2019 (COVID‐19) pandemic caused colleges of pharmacy to abruptly change teaching strategies mid‐semester in Spring 2020 due to campus closure and transition to remote learning. The objective of this study was to evaluate the effects of pandemic‐induced remote learning on student skill acquisition in a third year pharmacy student (P3) Pharmacists' Patient Care Process (PPCP) capstone course.MethodsStudent performance on weekly quizzes and mid‐term and final practical examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In one study the teaching included remote synchronous learning, 41 three studies used the Zoom videoconferencing platform, 39,41,42 two studies used the University platform Blackboard Collaborate 40 and one study also used the University Supported Management System: CANVAS. 41 The outcomes of interest that were explored were competency (n=2), 39,40 confidence (n=2), 40,41 knowledge (n=2), 39,41 skills (n=2) 41,42…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study the teaching included remote synchronous learning, 41 three studies used the Zoom videoconferencing platform, 39,41,42 two studies used the University platform Blackboard Collaborate 40 and one study also used the University Supported Management System: CANVAS. 41 The outcomes of interest that were explored were competency (n=2), 39,40 confidence (n=2), 40,41 knowledge (n=2), 39,41 skills (n=2) 41,42…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used a pre-test/post-test design, 40,41 the remaining two reported a post-test only study design, with a comparison between the study population and an earlier (pre-COVID) cohort of students. 39,42…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations